Advances in cellulosic conversion to fuels: engineering yeasts for cellulosic bioethanol and biodiesel production. (April 2018) - Ko, Ja Kyong; Lee, Sun-Mi
Graphical abstract: Highlights: Metabolic engineering improves microbial production of cellulosic fuels. We highlight a paradigm shift in engineering of ethanol producer, S. cerevisiae . Strain engineering focuses on improving carbon utilization and stress tolerance. An oleaginous yeast, Y. lipolytica, is an emerging cellulosic biodiesel producer. Abstract : Cellulosic fuels are expected to have great potential industrial applications in the near future, but they still face technical challenges to become cost-competitive fuels, thus presenting many opportunities for improvement. The economical production of viable biofuels requires metabolic engineering of microbial platforms to convert cellulosic biomass into biofuels with high titers and yields. Fortunately, integrating traditional and novel engineering strategies with advanced engineering toolboxes has allowed the development of more robust microbial platforms, thus expanding substrate ranges. This review highlights recent trends in the metabolic engineering of microbial platforms, such as the industrial yeasts Saccharomyces cerevisiae and Yarrowia lipolytica, for the production of renewable fuels.